Benefits of sustainable rural tourism: a case of Nqileni village, Eastern Cape Province, South Africa - Tshepiso Jonathan Setokoe; Takalani Ramukumba (African Journal of Hospitality, Tourism and Leisure, 2019)
The development of tourism has been heralded to bring to host communities benefits often deemed to alleviate poverty and reduce vulnerability in rural areas in the world. This has resulted in governments taking a keen interest in the development of tourism with the core focus being placed on the sector’s ability to contribute to economic development, thereby delivering on the mandate of improving the lives of the citizenry. Such efforts have been seen to go beyond economic benefits and extend into the concerted search for solutions aimed at redressing the effects of ecological and social crises resulting from massive exploitation of resources and the continuous degradation of the environment (social and physical). This relates to a definition widely promulgated following the Brundtland Commission (1987), namely that, ‘development that meets the needs of the present generation without compromising the ability of future generations to meet their needs’. The study analysed the benefits of sustainable tourism in rural communities both tangible and intangible in Nqileni village, Eastern Cape Province, South Africa. This was undertaken using a qualitative research approach using semi-structured interviews to solicit data from twenty five members of the Nqileni village community in their different capacities within the community. The data was analysed using the NVivo system, version 11. The study found that community members felt that sustainable tourism was creating benefits of socio-economic in nature and integrity of place.